Development of Kombucha Tea with Gac and Mango Fruits: Sensory, Nutritional, Phytochemical, Physicochemical and Antioxidant Evaluation - Nurus S.A. Aziz, Nurus S.A. Aziz; Mohd F.A Bakar, Mohd F.A Bakar; Dzulkarnain F.M. Farid, Dzulkarnain F.M. Farid; Tri B. Juliant, Tri B. Juliant (2023)
Kombucha tea is a sweetened black tea beverage that undergoes fermentation with a starter culture of bacteria and yeast (SCOBY). In this study, gac (Momordica cochinchinensis) and mango (Mangifera indica) fruits were primarily chosen for infusion into kombucha due to their health benefits. Thus, thisresearch aims to develop kombucha black tea with gac and mango, evaluate the sensory evaluation of the kombucha tea, and analyse the nutritional composition, physicochemical, phytochemical, and antioxidant activity of the kombucha tea. In this study, kombucha was prepared by fermenting black tea with sugar at different concentrations (70, 80, and 100 g) and SCOBY for 10 days before infusing it with gac and mango fruits. The sensory evaluation was evaluated using a hedonic 9-scale and another while using the standard methods. The result showed that kombucha gac and mango fruit with100 g of sugar (KGM100) represents the highest score on all attributes with a value of colour 7.5±1.55, aroma 6.47±1.74, taste 6.6±1.77, and overall, of 6.6±1.77. The nutrient of KGM 100 was higher than other concentrations with a value content of carbohydrates 6.9% and vitamin C of 2.70 mg/kg. The phytochemical of all samples showed increment during fermentation time and the antioxidant activity is higher in KGM100 (95.88%) while the physicochemical properties showed an increase in acidity and a decrease in colour. These findings show that kombucha black tea with gac and mango may impact health when consume and future investigation is worthy to determine its potential health benefits.